THE EFFECT OF TRAINING AND DEVELOPMENT, COMPENSATION AND ORGANIZATIONAL POLICIES ON THE PERFORMANCE OF EMPLOYEES OF THE REGIONAL REVENUE AGENCY OF RIAU ISLANDS PROVINCE - Yunita, Mira; Mon, Muhammad Donal (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
The purpose of this study was to determine the effect of training and development, compensation, and organizational policies on employee engagement and to determine the mediating role of employee engagement in the relationship between training and development, compensation, and organizational policies on employee performance. The number of samples used was 201 employees spread across 7 districts/cities in the working area of the Riau Island Regional Revenue Agency. Data collection was carried out using a questionnaire that was distributed via Google form using the Partial Least Square (PLS) data analysis method. The results of the study reveal that training and development, compensation, and organizational policies have a positive and significant impact on employee engagement. Employee engagement mediates the relationship between the independent variables and have a positive and significant impact on employee performance.